British influence on the federation of the Australian colonies, 1880-1901 - De Garis, B; De Garis, B. K. (1966)
﻿ Despite the obvious importance of federation in the political and general history of Australia it has received surprisingly little attention from historians. The three major accounts of the federal movement by Deakin, Wise, and Quick and Garran, were all written during or immediately after the events narrated, by men who had participated in them; though each is a valuable primary document, all exhibit inevitable limitations of bias and concentration on those aspects of the subject best known to the author. The only full length academic study of the federal movement, H.L.Hall's, Victoria's Part in the Australian Federal Movement (London,1931), relies heavily on the earlier accounts, concentrates narrowly on one colony, and is generally disappointing. The excellent scholarly articles more recently published by Parker, Blainey, Bastin, Martin, McMinn, MacCallum et al have been concerned mainly with the reassessment of the role of a few key individuals, and discussion of the significance of economic factors in promoting federation. The general emphasis of the whole corpus of material available is on the domestic politics associated with the federal movement with particular reference to New South Wales and to the eighteen-nineties. [Please see pdf. for full abstract.]